Tissue specific considerations in implementing high intensity focussed ultrasound under magnetic resonance imaging guidance - deSouza, Nandita M.; Gedroyc, Wladyslaw; Rivens, Ian; ter Haar, Gail (Frontiers in Oncology, 2022)
High-intensity focused ultrasound can ablate a target permanently, leaving tissues through which it passes thermally unaffected. When delivered under magnetic resonance (MR) imaging guidance, the change in tissue relaxivity on heating is used to monitor the temperatures achieved. Different tissue types in the pre-focal beam path result in energy loss defined by their individual attenuation coefficients. Furthermore, at interfaces with different acoustic impedances the beam will be both reflected and refracted, changing the position of the focus. For complex interfaces this effect is exacerbated. Moreover, blood vessels proximal to the focal region can dissipate heat, altering the expected region of damage. In the target volume, the temperature distribution depends on the thermal conductivity (or diffusivity) of the tissue and its heat capacity. These are different for vascular tissues, water and fat containing tissues and bone. Therefore, documenting the characteristics of the pre-focal and target tissues is critical for effective delivery of HIFU. MR imaging provides excellent anatomic detail and characterisation of soft tissue components. It is an ideal modality for real-time planning and monitoring of HIFU ablation, and provides non-invasive temperature maps. Clinical applications involve soft-tissue (abdomino-pelvic applications) or bone (brain applications) pre-focally and at the target (soft-tissue tumors and bone metastases respectively). This article addresses the technical difficulties of delivering HIFU effectively when vascular tissues, densely cellular tissues, fat or bone are traversed pre-focally, and the clinical applications that target these tissues. The strengths and limitations of MR techniques used for monitoring ablation in these tissues are also discussed.